Notes on Refinable Functions (Journal of Computational Mathematics, 1998)
In this paper some  properties of refinable functions and some relationships between the mask symbol and the refinable functions are studied. Especially, it is illustrated by examples that the linear spaces formed by the translates over the lattice points of refinable functions may contain polynomial spaces of degree higher than the smooth order of the corresponding refinable functions.
Keywords: Mask; Symbol; Refinable Function.